Synthesis and Antimicrobial Activity of Substituted N-(1-piperidinobenzyl)- Nicotinamide: A Structure-Reactivity Study - Raman, N.; Ravichandran, S. (Asian Journal of Chemistry, 2010)
Substituted N-(1-piperidinobenzyl)nicotinamide compounds have been prepared and characterized by IR, UV and 1H-NMR spectral analysis. The antimicrobial activities of the compounds have been studied.